Simultaneous presence of multiple Campylobacter species in dogs - Koene, M G J; Houwers, D J; Dijkstra, J R; Duim, B; Wagenaar, J A (Journal of clinical microbiology, 2004)
The prevalence of coinfection of Campylobacter species in dogs was determined using four isolation methods. In 26% of the positive-testing stools, multiple Campylobacter species were identified. The use of multiple isolation methods as well as the time lapse between sampling and processing are important for detection of coinfection.